LITERATURE REVIEW DETERMINATION OF MERGER AND ORGANIZATIONAL CULTURE CHANGE: ANALYSIS OF TRANSFORMATIONAL LEADERSHIP AND EMPLOYEE REACTIONS (A STUDY OF HUMAN RESOURCE MANAGEMENT LITERATURE) - Ganjar Pranajaya (Dinasti International Journal of Education Management And Social Science, 2022)
The rapidly growing business world indirectly requires every company to be able to optimize its resources, including capital, machinery, raw materials, human resources, and many others. Of the many resources owned by the company, human resources are very important resources, especially companies that are in a merger collaboration, there must be a lot of human resources involved in achieving company goals so good leadership and cooperation are needed in all fields both individuals and between departments within the company. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are that: 1) Transformational Leadership has an effect on Mergers; 2) Employee reactions affect the Merger; 3) Transformational Leadership influences Organizational Culture; 4) Employee reactions affect the Organizational Culture; and 5) Organizational Culture affects the Merger.